Ultra-low cycle fatigue (ULCF) in fibre-reinforced concrete beams. (August 2022) - Accornero, Federico; Rubino, Alessio; Carpinteri, Alberto
Highlights: The updated Bridged Crack Model is able to describe ultra-low cycle fatigue in FRC beams; New constitutive laws are proposed to describe the hysteresis of fibre-reinforcements; FRC post-cracking regime depends on two dimensionless numbers: N P and N w ; The Bridged Crack Model model effectively predicts the hysteretic dissipated energy. Abstract: Civil structures subjected to extreme loading conditions, e.g., earthquakes, undergo large deformations and fracture due to ultra-low cycle fatigue (ULCF). Although several efforts have been made to understand and to model monotonic damage and low-cycle fatigue, so far ULCF is neither sufficiently investigated nor understood. In the present work, ULCF of fibre-reinforced concrete (FRC) beams subjected to bending is discussed in the framework of Fracture Mechanics by means of the Updated Bridged Crack Model (UBCM). The model focuses on the evolution of the fracturing process at the critical cross-section of the beam, taking into account the loading reversal. The concrete matrix is assumed to be linear-elastic and perfectly-brittle. On the other hand, the toughening contribution of the reinforcing fibres is described by a constitutive law that defines the hysteretic behaviour at the single fibre level. The suitability of the hysteretic constitutive law is discussed on the basis of experimental results recently reported in the current scientific literature, in which ULCF flexural tests were carried out on FRC specimens.